جهود التيار الإستقلالي و الثورة التحريرية الجزائرية في كسب الرأي العام الخارجي ضد المحتل الفرنسي - سالم, اسماء; ديه, نهلة (جامعة الوادي - University of Eloued, 2023)
تتناول هذه الدراسة الموسومة بعنوان: جهود التَّيَّار الاستقلالي والثورة التحريرية في كسب الرأي العام الخارجي ضد المحتل الفرنسي (1926) - 1962م)، أهم المحطات لجهود كل من التيار الاستقلالي والثَّورة التَّحريريَّة في كسب الرأي العام الخارجي ضد الاحتلال الفرنسي منذ سنة 1926م حتى الاستقلال سنة 1962م مروراً بأهم الأحزاب والهيئات المشكلة لهما، وأهم نشاطاتهما الداخلية والخارجيَّة ؛ وبالوقوف عند الحكومة الجزائرية المؤقتة التي كانت كواجهة سياسية للمرافعة على تدويل القضيَّة الجزائرية والدفاع عن الحريات العامة للشعب الجزائري. ودور الصحافة المكتوبة في دعم وتدويل القضية إلى غاية نيل الجزائر لاستقلالها سنة1962 . This study, entitled: The efforts of the independence movement and the liberation revolution in gaining foreign public opinion against the French occupier (1926-1962), deals with the most important stations of the efforts of both the independence movement and the liberation revolution in gaining external public opinion against the French occupation from 1926 until independence in 1962. Going through the most important parties and bodies formed for them, and their most important internal and external activities, and standing with the Algerian interim government, which was a political front to plead the internationalization of the Algerian cause and defend the public freedoms of the Algerian people. The role of the written press in supporting and internationalizing the cause until Algeria gained its independence in 1962.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: التيار الاستقلالي - الثورة التحريريَّة - الرَّأي العام الخارجي – الاحتلال الفرنسي - الحكومة المؤقتة - القضية الجزائرية; The independent current - Liberation Revolution - External public opinion the French occupation - the provisional government - The Algeriancase.